Legal Policy Against the Crime of Women Trafficking in Indonesia - Adnani, Adriani; Kurnia, Meita Lefi (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
The National Commission Against Violence against Women, also known as Komnas Perempuan, was established over a decade ago in Indonesia. The ratification of numerous policies to protect women also applies in this situation. Paradoxically, there continues to be a significant number of crimes targeting women, with one such crime being the act of trafficking women. The problem is being defined as follows: 1. What is the legal framework governing the offence of human trafficking in women in Indonesia? The implementation of legal policy against the crime of trafficking in women in Indonesia is assessed. Indonesia's legal policy on criminal trafficking of women has been regulated, but its implementation has not been optimal. This is evident from the increasing number of trafficking cases in the country. The Indonesian government needs to take appropriate measures to reduce or minimize these criminal acts. This can enhance underlying variables, such as economic, social, cultural, and political advancements.